2020
DOI: 10.1097/j.pain.0000000000002028
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, randomized, placebo-controlled crossover trial of alpha-lipoic acid for the treatment of fibromyalgia pain: the IMPALA trial

Abstract: Fibromyalgia is a common and challenging chronic pain disorder with few, if any, highly effective and well-tolerated treatments. Alpha-lipoic acid (ALA) is a nonsedating antioxidant with evidence of efficacy in the treatment of symptomatic diabetic neuropathy that has not been evaluated in the setting of fibromyalgia treatment. Thus, we conducted a single-centre, proof-of-concept, randomized, placebo-controlled, crossover trial of ALA for the treatment of fibromyalgia. Twenty-seven participants were recruited,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…Thus, our observation of no added benefit with combination therapy is not related to inadequate drug dosing. Despite evidence of efficacy of ALA for the treatment of painful diabetic neuropathy, recently reported evidence that ALA monotherapy does not reduce pain in fibromyalgia 14 is one obvious explanation for our observations. Even if ALA has no efficacy as a monotherapy for fibromyalgia, its described inhibition of nociceptive T-type calcium (Cav3.2) channels 26 that differ from those inhibited by pregabalin, ie, N-type calcium channels, 36 provided a mechanistic rationale for a possible beneficial interaction between pregabalin and ALA, which we unfortunately did not observe.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Thus, our observation of no added benefit with combination therapy is not related to inadequate drug dosing. Despite evidence of efficacy of ALA for the treatment of painful diabetic neuropathy, recently reported evidence that ALA monotherapy does not reduce pain in fibromyalgia 14 is one obvious explanation for our observations. Even if ALA has no efficacy as a monotherapy for fibromyalgia, its described inhibition of nociceptive T-type calcium (Cav3.2) channels 26 that differ from those inhibited by pregabalin, ie, N-type calcium channels, 36 provided a mechanistic rationale for a possible beneficial interaction between pregabalin and ALA, which we unfortunately did not observe.…”
Section: Discussioncontrasting
confidence: 84%
“…2C, overall P = 0.54). Given a trend for differences between men and women in the effects of ALA in our previous fibromyalgia trial, 14 we conducted an exploratory sex-based or gender-based analysis of average daily pain. Recognizing the limitations in statistical power (because there were only 4 male participants in this trial), this exploratory analysis revealed that average pain for men was 4.6, 4.5, and 5.0 for ALA, pregabalin, and combination, respectively with no statistically significant differences ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Low back pain is one of the disease that wreaks more havoc on people's lives (6)(7)(8). Other leading causes and conditions of chronic pain are Rheumatoid arthritis (9)(10)(11), Shoulder Pain (8), Headache disorders (12,13), Cancer (14,15), Fibromyalgia (16,17), Cervical and Thoracic Pain (18).…”
Section: Introductionmentioning
confidence: 99%
“…α-lipoic acid (ALA, thioctic acid (5-(1,2-dithiolan-3-yl)pentanoic acid) is a usually considered as "universal antioxidant". It is a naturally occurring antioxidant found in foods like meat, spinach, and cabbages [13][14][15]. It is synthesized in small amounts by plants and animals, including humans and it functions as an essential co-factor for several mitochondrial multi-enzyme complexes involved in energy metabolism [16].…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies, ALA has shown bene cial effects against cardiovascular dysfunction [17], sepsis [18], endothelin dysfunction and oxidative stress [19], testicular dysfunction [20] and liver dysfunction [21]. Recently, ALA has been clinically tested for its bene cial effects in patients with bromyalgia pain [14], multiple sclerosis [22], obesity [23], β-thalassemia [24], diabetes [25], non-alcoholic fatty liver disease [26]. In the cancer perspective, the anticancer potential of ALA was investigated against a variety of cancer cell lines including lung neuroblastoma, breast, leukemia and hepatoma [27][28][29][30][31] Clinically, ALA was undergone a phase II clinical trial against anticancer drug-induced alopecia in breast cancer patients [32] and chemotherapy-induced peripheral neuropathy [33] Therefore, it is reasonable to assume that ALA could be an effective agent against OSCC.…”
Section: Introductionmentioning
confidence: 99%